Certificate of Joseph Francis Van Horsigh - Van Horsigh, Joseph Francis
Certificate admitting Van Horsigh to a religious order in Mechelen, Belgium.
Belgian monk.
Collection material in Latin.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Monks; Monasticism and religious orders -- Belgium -- Mechelen; Clergy